Evaluating the Role of Artificial Intelligence on ESG Reporting : Evidence from India - Mohapatra, Amiya Kumar; Matta, Rahul; Soni, Rashmi; Hiremath, Nandeesh V. (Prabandhan: Indian Journal of Management, 2024)
Purpose : This paper investigated how artificial intelligence (AI) technologies influence ESG reporting by examining 253 selected publicly listed companies in India from 2016 to 2023. Methodology : This study applied multiple regression analysis to measure the influence of artificial intelligence on ESG (Environmental, Social, and Governance) performance of the companies toward sustainability. The combined ESG scores and individual ESG pillar scores were derived from the Refinitiv database, and content analysis was employed to measure the artificial intelligence (AI) score. Findings : The results indicated that AI positively and significantly influenced the overall ESG, environmental, and governance scores. However, results showed a negative relationship between AI and social score. Further, the results indicated that AI was positively influenced by board characteristics, such as the board of director’s size, frequency of meetings, and board independence in strategic initiatives. In recent years, companies have become more informed about AI’s adoption, benefits, and implications within business. Also, the low AI scores suggest that some companies are still in the early stages of adoption of AI. Practical Implications : This study extended the existing literature and widened the scope of stakeholders’ theory. By addressing stakeholder concerns through AI, companies can enhance trust, reputation, and long-term viability, ultimately reducing the likelihood and impact of adverse events. Originality : This study extended the present-day literature by empirically testing how AI can influence the ESG performance of companies, including its potential impact on the individual dimensions or pillars of the overall ESG frameworks.